Use of Lawsonia Inermis and Sodium Nitrite as Surface Applied Corrosion Inhibitors - Nishant Kumar; Saharan, Sunil (International Journal of Sustainable Construction Engineering and Technology, 2022)
This research provides an investigation to measure the rate of corrosion of steel bars coated with organic corrosion inhibitor Lawsonia inermis (Henna) and inorganic corrosion inhibitor Sodium Nitrite (NaNO2) embedded in concrete. Presence of corrosion on the reinforcement bars reduces the bond strength between steel and concrete over a while and excessive corrosion on reinforcement bar can lead to loss of ductility, strength and in extreme cases collapse. Structures like marine structures, sewage pipes, which are prone to damage due to presence of excessive salts, acidic environment, the corrosion rate is accelerated when compared to normal structures, therefore there is need of protecting such type of structures. In previous researches, the corrosion inhibitors were added directly into the mix while preparing the concrete mix and inhibition efficiency was analysed. However, in this case, the corrosion inhibitors are applied to the reinforcing bars itself as the corrosion occurs on the bars and which has proven to be effective. In the present study, the reinforcement bars are coated with Henna paste and Sodium Nitrite paste as corrosion inhibitors. Inhibitors in the form of 2 layers, 4 layers and a combination were used. The beams specimens were cured for 58 days in saline environment. The difference in the corrosion potential is measured by half-cell potentiometer. Results suggested that the specimen with 4 layers of Henna coating had reduced the rate of corrosion by 46% when compared to original sample.  Also, specimens with 2 coats of Henna and 4 coats of Henna and sodium nitrite showed better corrosion inhibition efficiency.